The Influence of Job Satisfaction, Leadership and Organizational Justice on Employee Well-Being - Atalya Fransiska; Joyce A. Turangan (Graduate Program of Universitas Tarumanagara, 2023)
Employee well-being should be felt by the workers who work in the company. By being able to feel the well-being of the workers, it can help the company to increase the productivity and performance of the workers without asking for it. However, employee well-being will not be realized by itself. The company needs some support through job satisfaction, leadership as well as existing organizational justice. The sampling technique used is convenience sampling with a total of 90 respondents who are employees of PT Lancar Makmur Bersama. Data processing is done using SmartPLS software. The results of this study are job satisfaction, leadership and organizational justice each have a positive influence on employee well-being. Job satisfaction, leadership and organizational justice also have a significant relationship to employee well-being. This paper presents insights that can be used as reference material for further researchers related to the variables of job satisfaction, leadership and organizational justice and employee welfare. In addition, this paper also presents insights that can be used as criticism and suggestions for companies related to job satisfaction, leadership and organizational justice so that later they can improve or maximize employee well-being in the company.